Odpowiedzi

2010-03-19T16:49:23+01:00
A)3*(x+4)/3 = x+4
b)4*(2y-1)/4=2y-1
c)5*(-2a+3)/5 + 6*(2a-3)/6=-2a+3+2a-3=0
d) 7*(2x-3)/7 - 8*(8-2x)/8=2x-3 -8+2x=4x-11
4 4 4
2010-03-19T16:50:43+01:00
A)3x+12/3=3(x+4+1)=3x+12+3=3x+15
b) 8y-4/4=4(2y-1/1)=8y-1
c)-10a+15/5+12a-18/6=5(-2a+3/1)+6(2a-3/1)+-10a+3+12a-3=2a
d)14x-21/7-64-16x/8=7(2x-3/1)-8(8-2x/1)=14x-3-64+2x=16x-67
1 1 1
2010-03-19T16:59:14+01:00
3x+12/3=3(x+4/1)=3(x+4)
8y-4/4=4(2y-1/1)=4(2y-1)
-10a+15/5+12-12a-18/6=-10a+3+12-12a-3=-22a+12=2(-11a+6)
14x-21/7-64-16x/8=14x-3-64-2x=12x-67
1 1 1